Studying online from home and social anxiety among university students: The role of societal and interpersonal mattering - Ahmad Naufal Fawwaz; Kususanto Ditto Prihadi; Endah Kurniawati Purwaningtyas (International Journal of Evaluation and Research in Education (IJERE), 2022)
Literature suggested that the enforcement of lockdowns such as the Movement Control Order (MCO) had limited physical social interaction and therefore increased the inclination on social media and other means of digital communication. This shift of social pattern was reported to alter the way young adults develop their mattering, the sense of how much they matter to others. While mattering has been reported as the protective factors against social anxiety, this study aims to investigate the contribution of interpersonal mattering and societal mattering on social anxiety among university students who had to study online from home during the enforcement of the MCO in Malaysia amidst the COVID-19 pandemic in early 2021. Purposive sampling was conducted to recruit 158 participants (89 females, 69 males) with their ages ranging from 18 to 25 years of age (M=21.77, SD=1.54) to respond to Mattering to Others Questionnaire, University Mattering Scale, and Social Phobia Inventory. The results of multiple linear regression supported the hypotheses that both types of mattering negatively predict social anxiety, and that interpersonal mattering was no longer a significant predictor when controlling for societal mattering.